A Discursive trap? the power and danger of the middle-income trap discourse - Curato, Nicole C. (2018)
The "middle-income trap" has gained currencu in the past decade among economics and development practitioners. The term draws attention to countries that have experienced rapid economic growth but failed to break through the high-income status. This article critically examines the underlying discursive logics behind the vocabulary of the middle-income country trap. The term may seem technical and benign, but its ontology, assumptions, rhetorical devices, and conception of economic actors privilege a sequential view of economic development bereft of normative considerations and ethical standpoints.
Keywords: Economic development